Expression levels of caspase‐3 and gasdermin E and their involvement in the occurrence and prognosis of lung cancer - Yuan‐Li Huang; Guang‐Hui Zhang; Qing Zhu; Xia Wu; Li‐Gao Wu (Cancer Reports, 2022)
Abstract Background Pyroptosis plays a dual role in the development of cancer and malignancy; as such, it may potentially be a new target for cancer treatment. However, the inflammatory response to pyroptosis may have adverse effects on the body. The roles of gasdermin E (GSDME), caspases, and related proteins associated with pyroptosis in cancer remain controversial. Aim The goal of this study was to determine whether the expression levels of caspase‐3 and GSDME affect the clinical stage, pathological grade, or survival prognosis of patients with lung cancer. Methods We examined the protein levels of GSDME, caspase‐3, caspase‐8, and caspase‐9 in lung tissue samples from 100 patients with lung cancer by using immunohistochemistry. Results We found that GSDME, caspase‐3, and caspase‐8 were more highly expressed in tumor tissues than in adjacent normal tissues. Moreover, we found that GSDME could serve as a prognostic factor as there was a positive correlation between its expression level and the postoperative survival rate of patients with lung cancer. Conclusions GSDME may be an independent factor affecting the prognosis of patients with lung cancer. However, the role of GSDME and its related proteins in cancer requires further research.